2018
DOI: 10.2220/biomedres.39.251
|View full text |Cite
|
Sign up to set email alerts
|

<b>1</b><i><b>O</b></i><b>, 20</b><i><b>O</b></i><b>-diacetyl kamebakaurin protects against acetaminophen-induced hepatotoxicity in </b><b>mice </b>

Abstract: The present study aimed to investigate the protective effects of kamebakaurin (KA) and 1O, 20O-diacetyl kamebakaurin (Ac 2 KA) on acetaminophen (APAP)-induced hepatotoxicity and compare the hepatoprotective mechanisms of the two chemicals. Seven-week-old male C57BL/6J mice were orally administered KA, Ac 2 KA, or an ethanol/olive oil emulsion once per day for 7-days. Twenty-four hours after the final administration, the mice were fasted and then intraperitoneally injected with 450 mg/kg APAP or saline. At 16 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[ 52 ] It represents about 13% of CYP enzymes in the human liver, and is involved, among others, in APAP metabolism. [ 56–58 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 52 ] It represents about 13% of CYP enzymes in the human liver, and is involved, among others, in APAP metabolism. [ 56–58 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, this inhibitor has been implicated in playing a role related to APAP-induced hepatotoxicity (Henderson et al, 2007;Schwabe et al, 2003). Since our previous analysis showed that APAP-induced c-Jun N-terminal kinase phosphorylation is attenuated by Ac 2 KA (Yoshioka et al, 2018), this hypothesis is plausible. Saito et al showed that NAC post-administration has two effects: enhancing hepatic glutathione levels and support- (n = 5-7 per group).…”
Section: Discussionmentioning
confidence: 91%
“…Our previous investigation indicated that 1O, 20Odiacetyl kamebakaurin (Ac 2 KA), which is synthesized from kamebakaurin, prevents APAP-induced hepatic injury by inhibiting lipid peroxidation and inflammatory responses (Yoshioka et al, 2018). Although Ac 2 KA was found to exert a good protective effect, our previous study only evaluated the pre-treatment effects of Ac 2 KA.…”
Section: Introductionmentioning
confidence: 99%
“…Losartan administration caused an improvement in serum TAS, GSH, TOS, GSSG, and MDA levels depending on the dose. In studies evaluating the protective efficacy of Tinospora cordifolia and Boerhavia diffusa extracts, irbesartan, n-acetylcysteine, and taurine in hepatotoxicity induced by acetaminophen; it has been shown that these test substances cause an increase in GSH and TAS levels after acetaminophen injection and a decrease in TOS, GSSG, and MDA levels (Acharya and Lau-Cam 2010 ; Kaushik et al 2017b ; Yoshioka et al 2018 ; Helal and Samra 2020 ). The improvement in TAS, GSH, TOS, GSSG, and MDA levels, which are oxidative stress markers, can be considered an indication that losartan has a protective and curative effect by reducing oxidative stress in hepatotoxicity induced by acetaminophen.…”
Section: Discussionmentioning
confidence: 99%